Answer:
7
Step-by-step explanation:
1. Subtract the 4x on both sides = -14 = -2x
2. Divide -2 on both sides to get -14/-2 = x
3. -14/-2 = 7 so 7 = x
<h3>
Answer: Choice A</h3>
What we do is simply replace every n with k+1. So (3n)^2 turns into (3(k+1))^2
We see that only choice A has the correct term mentioned on the left hand side, so this must be the answer.
The right hand side is treated the same way. We plug in n = k+1. Your teacher did a bit of algebraic manipulation to get what is shown for choice A.
Answer:
5 2/3 I think
Step-by-step explanation:
divide 68 by 12
Area = 1/2 * base * height = 1/2 * 5 * 3 3/4 = 9 3/8 or 9.375 in^2
Answer:
27/40
Step-by-step explanation: